Serum Catestatin Level in Preeclampsia - Alghazali , Basima Sh; Mahdi, Tabarak Karim (Scripta Medica, 2024)
Background/Aim: Preeclampsia, a significant cause of maternal morbidity and mortality, is linked to increased cardiovascular risks. Catestatin regulates cardiovascular function which indicates its usefulness in understanding pathophysiology of preeclampsia and its severity. Aim of this study was to evaluate association of catestatin in preeclamptic women and control non preeclamptic women and assess its association with presence and severity of preeclampsia. Methods: A case-control study at Al-Zahraa Teaching Hospital, Iraq, performed from January to December 2023 involved 90 pregnant women: 30 with severe preeclampsia, 30 with mild preeclampsia and 30 healthy controls. Inclusion criteria were preeclamptic pregnant women at 27-40 weeks of gestation and age ranging from 20-40 years and similar non-eclamptic controls. Exclusions were smokers, chronic drug users and those with chronic illnesses. Data collection included general and clinical information, BMI, vital signs, examinations and laboratory tests including serum catestatin. Results: Catestatin levels varied significantly among severe preeclampsia, mild preeclampsia and control groups. Average catestatin level in severe preeclampsia group was markedly lower at 29.01, compared to 43.67 in mild preeclampsia and 59.96 in controls. The diagnostic performance of catestatin for severe preeclampsia was notable, with a cutoff point of ≤ 37.165, sensitivity of 80 % and specificity of 83.3 %, highlighting its potential as a critical biomarker in preeclampsia evaluation. Conclusion: Catestatin level was significantly lower in sever preeclampsia compared to mild and control group, which may indicate its association with preeclampsia. Lower catestatin in sever preeclampsia suggest its inverse relation with preeclampsia severity.
Keywords: Catecholamines; Chromogranins; Chromogranin A; Preeclampsia